Melanomas in ophthalmology - Meerhoff, Walter (Cirugía del Uruguay, 1974)
Comrnents were made on the clinicopathologic, diagnostic, therapeutic and prognostic problems which arise in ophthalmologic melanomas. Although prognosis is less severe than in the others parts of the body ( especially in sorne intraocular localizations) their behaviour is as enigmatic and disconcerting as in the latter. Importance is given to the histological elements which, taken from authentic statistics, make it possible uveal tract (iris, ciliary body and choroids) and of the conjuntiva, emphasizing the importance of their pecularities which must be taken into consideration in treating each particular case.